2011
DOI: 10.1080/15017419.2010.507374
|View full text |Cite
|
Sign up to set email alerts
|

Descriptions of children's needs and parenthood among mothers with intellectual disability

Abstract: This study looks at how mothers with an intellectual disability describe their children's needs, their own parenting and parenthood, and their encounters with professionals providing them with help and support. The analysis draws upon a relational perspective on disability, theories of modern parenthood, and the concept of the sense of coherence in examining the strategies used by the interviewed mothers in their everyday lives, such as consulting people they trust. Having a child and being entrusted with the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
4
0
3

Year Published

2013
2013
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 24 publications
2
4
0
3
Order By: Relevance
“…The negative experiences with health professionals reported by the disabled women are generally in accord with the results of previous studies (see Malacrida 2009;Starke 2011;Walsh-Gallagher et al 2013). As noted before, the medicalization of pregnancy emphasizes the expert knowledge in family planning of health professionals.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…The negative experiences with health professionals reported by the disabled women are generally in accord with the results of previous studies (see Malacrida 2009;Starke 2011;Walsh-Gallagher et al 2013). As noted before, the medicalization of pregnancy emphasizes the expert knowledge in family planning of health professionals.…”
Section: Discussionsupporting
confidence: 89%
“…The earlier studies on the experiences of motherhood by disabled women with different kinds of impairment have mainly focused on their practical mothering of their children (Aune 2013;Grue and Lӕrum 2002;Lawler, Begley, and Lalor 2015;Malacrida 2009;Prilleltensky 2004) or on their experiences with social services and health care professionals (Starke 2011;Thomas 1997;Walsh-Gallagher et al 2013). Only a few studies (Johnson et al 2001;Prunty et al 2008) have investigated the choice or decision by disabled women to become a mother.…”
Section: Introductionmentioning
confidence: 99%
“…On the other, it cannot be ruled out that this is a manifestation of the paradox referred to in the introduction [6]. A similar trend in mothers with intellectual disabilities raising children with developmental delays was reported by M. Starke [38]. Mothers interviewed in the study primarily emphasized positive aspects of their children's functioning and the fact that child raising was the source of their personal growth.…”
Section: Conclusion and Discussionsupporting
confidence: 62%
“…Previous research has shown that a very low percentage of people with IDs are parents, which restricts the number of friends with IDs who have children and if they are parents their children are often taken care of by social services in foster homes (Booth 2003;Starke 2011). These experiences are shared by the interviewees in this study.…”
Section: The Difficulties Of Parenthood and Of Building Relations Witmentioning
confidence: 79%
“…Today, research tries to discern the social barriers and restrictions which affect individuals' with IDs abilities to parent (Llewellyn et al 2010;Starke 2011). Research has so far been more occupied with parents with IDs and the societal resistance towards them than with women and men with IDs who choose not to become parents.…”
Section: Historical Background On Parenthood For Disabled Individualsmentioning
confidence: 99%